2017
DOI: 10.15252/embj.201797813
|View full text |Cite
|
Sign up to set email alerts
|

Wnt activity and basal niche position sensitize intestinal stem and progenitor cells to DNA damage

Abstract: The authors state that it came to their attention that the figure legends of two figures were not sufficiently detailed in the original version of the manuscript.The figure Representative Western blots of cell lysates for the expression of phospho-p53 and cleaved caspase-3 (each n = 3; see Source Data for this figure). Samples from a single experiment were divided into identical portions and probed for phospho-p53 or cleaved casp3. The expression control of beta-actin was conducted on the second aliquot of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…In this situation, Lgr5-expressing ISCs were particularly susceptible to radiation exposure, and could be almost completely ablated by high doses of radiation. 30,62,63 In contrast, Bmi1-expressing ISCs were not only radio-resistant, but lineage tracing output increased after exposure to radiation, 30 indicating that the þ4 quiescent ISCs were at least partly responsible for the regenerative response. In addition to cells that express Bmi1, 30 cell populations that express Hopx, 57,64,65 mouse Tert, 59,66 and other genes 63,[67][68][69] were found to have regenerative, ISC functions after epithelial damage, supporting a model in which quiescent þ4 ISCs can survive and participate in regeneration after loss of aISCs.…”
Section: þ4 Intestinal Stem Cellsmentioning
confidence: 99%
“…In this situation, Lgr5-expressing ISCs were particularly susceptible to radiation exposure, and could be almost completely ablated by high doses of radiation. 30,62,63 In contrast, Bmi1-expressing ISCs were not only radio-resistant, but lineage tracing output increased after exposure to radiation, 30 indicating that the þ4 quiescent ISCs were at least partly responsible for the regenerative response. In addition to cells that express Bmi1, 30 cell populations that express Hopx, 57,64,65 mouse Tert, 59,66 and other genes 63,[67][68][69] were found to have regenerative, ISC functions after epithelial damage, supporting a model in which quiescent þ4 ISCs can survive and participate in regeneration after loss of aISCs.…”
Section: þ4 Intestinal Stem Cellsmentioning
confidence: 99%
“…However, Tao et al have also shown that niche positioning determines the Wnt signaling activity of intestinal stem and progenitor cells (ISPCs), with ISPCs at the intestinal crypt bottom exhibiting higher Wnt/−catenin activity than the ISPCs located at higher positions of the crypt. ISPCs with higher Wnt signaling activity are preferentially depleted by irradiation-induced DNA damage [18]. Furthermore, instructed enhancement of Wnt signaling increases radio-sensitivity of ISPCs, while inhibition of Wnt signaling decreases it [18].…”
Section: Discussionmentioning
confidence: 99%
“…ISPCs with higher Wnt signaling activity are preferentially depleted by irradiation-induced DNA damage [18]. Furthermore, instructed enhancement of Wnt signaling increases radio-sensitivity of ISPCs, while inhibition of Wnt signaling decreases it [18]. These seemingly contradictory results from different studies on the role of Wnt signaling activity on fate and activities of ISPCs upon DNA damage might due to the different angles of the studies: Tao et al particularly looked at the early fate (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations